The economics of Ireland's property market bubble - Lyons, R; Ronan Lyons (2013)
This doctorate explores key aspects of the economics of housing by examining Ireland's housing market bubble of the early 2000s. For earlier chapters, the main source material is a previously unused dataset of almost two million property listings, covering the entire country from 2006 until 2012, maintained by property website daft.ie. An initial chapter outlines stylised facts of Ireland's housing market 2007-2012, including a greater spread of prices over property size in the crash but a narrower spread of rents. In contrast, the geographical spread of prices and rents was largely unchanged. The spread of rents was constrained relative to the spread of prices, suggesting either renter search thresholds or buyer "lock-in" effects. To examine which was at work, the daft.ie dataset is combined with information on a range of amenities, including landscape, transport, education, social capital and market depth. Overall, there is clear evidence that the rent effects of a range of amenities are smaller than the price effects. There is limited evidence of procyclical amenity pricing, which would indicate "lock-in" effects, with the analysis suggesting instead countercyclical pricing, or "property ladder" effects during the bubble. Results from these analyses are based on listed price and rents, rather than transaction prices. The relationship between the two is examined in a separate chapter, using an additional Central Bank of Ireland dataset on mortgages. The spread between list and sale prices gap that exists between the two is decomposed into four parts, a selection spread, a matching spread, a counteroffer spread and a drawdown spread. A selection spread of up to 10% emerged in the Irish housing market after 2009, while the counteroffer spread was positive before 2009 but negative for much of the period 2009-2011. The final chapter uses both inverted-demand and price-rent ratio methods to examine the long-run determinants of house prices in Ireland from 1980 on. In addition to careful treatment of standard fundamentals, it includes a measure of credit conditions as well as the ratio of persons to households, both contributions to the literature. The resulting inverted demand error-correction model shows a clear and stable long-run relationship, which is largely preserved when cointegration between series is explored. Similarly, a model of the price-rent ratio from 2000 shows clear error-correction properties. Together, they suggest that while a range of factors drove Irish house prices 1995-2001, credit conditions were largely responsible for the subsequent increase.